The Historical Foundations. Historical Architectural Treaty How Information Source of the Architectonic Heritage - Fernando Da Casa; Ernesto Echeverria; Flavio Celis (Geoinformatics FCE CTU, 2011)
In order to address architectural heritage conservation, we must be familiar with the medium with which we will be working, its function and response to incidents or external actions (natural or anthropogenic) and how the buildings were conceived and constructed in order to understand how they will be affected by the intervention process to which they will be subjected and adopt the adequate measures so these processes will not harm the buildings. An important element is the foundation. This is a fundamental, yet often forgotten, element. It is important to know the history of the foundations, how and why they were constructed and for this, it is essential to study architectural treatises as the origin of their design. It is surprising to read classical architecture treatises and observe that they do not refer to calculations of dimensions, but to constructive solutions that today may seem clever because they are obvious, but in reality, they do not address the thoughts of the designer or builder. The historic architectural treatises on construction that significantly influenced Spanish construction, which we studied and will present in this article, include Vitruvius and Palladio as well as the developments in the eighteenth and nineteenth centuries, and even into the first half of the twentieth century: (Vitruvius (1st century BC), Palladio (1524), Alberti (1582), Cristóbal de Rojas (1598), Fray Laurencio San Nicolás (1639), Brizguz y Bru (1738), Rieger (1763), Fornes y Gurrea (1841), Espinosa (1859), Marcos y Bausá (1879), Ger y Lobez (1898) and Barberot (1927).